2017
DOI: 10.1007/s13197-017-2748-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three pumpkin species: correlation with physicochemical, antioxidant properties and classification using SPME-GC–MS and E-nose methods

Abstract: To ascertain the most discriminant variables for three pumpkin species principal component analysis (PCA) was performed. Twenty-four parameters (pH, conductivity, sucrose, glucose, total soluble solids, ,, , individual weight, edible rate, firmness, citric acid, fumaric acid, l-ascorbic acid, malic acid, PPO activity, POD activity, total flavonoids, vitamin E, total phenolics, DPPH, FRAP, β-carotene, and aroma) were considered. The studied pumpkin species were, , and. Three pumpkin species were classified by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 37 publications
(61 reference statements)
4
42
1
3
Order By: Relevance
“…Table 3 shows that the ash content of instant porridge across treatments ranged between 1. 46 The ash content in this study was similar to 3.18% of pumpkin flour [53]. The Indonesian national Standard requires ash content not to exceed 3.5 g/100 g [55].…”
Section: ) Watersupporting
confidence: 62%
See 1 more Smart Citation
“…Table 3 shows that the ash content of instant porridge across treatments ranged between 1. 46 The ash content in this study was similar to 3.18% of pumpkin flour [53]. The Indonesian national Standard requires ash content not to exceed 3.5 g/100 g [55].…”
Section: ) Watersupporting
confidence: 62%
“…The essential components in pumpkin are 16,571.78 µg/100 g β carotene; 46.31% antioxidant activity and 0.06% phenol. The antioxidant activity expressed in Trolox had the equivalent value in pumpkin Cucurbita maxima, and Cucurbita moschata was 2.61±0.04 and 1.92±0.01 mmol/100 g, respectively [46]. The level of β carotene in pumpkin varied between 1.6 and 45.6 mg/100 g [47].…”
Section: A Basic Chemical Propertiesmentioning
confidence: 99%
“…There was significant difference ( p < 0.05) observed in ΔE* values of pumpkin extracts prepared with UAE and MAE. Zhou et al [ 44 ] analysed the colour attributes of three species of pumpkins i.e., Cucurbita maxima - L* = 38.08, a* = 3.30, b* = 17.60; Cucurbita pepo - L* = 32.67, a* = −0.13, b* = 1.68 and Cucurbita moschata - L* = 35.59, a* = 0.52, b* = 11.24. The variations in our results could be related with sample matrix where we used pumpkin extracts in corn oil and hexane/isopropyl alcohol (as the instrument is especially designed for solid or powdered samples); however, we calculated the colour parameters after subtracting the control sample readings from our treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Elinge et al [61] reported that Cucurbita pepo seeds contain calcium, magnesium, sodium, phosphorus, iron, zinc, manganese, and cobalt (Table 3). Regarding the vitamin content, it is well known that pumpkins are an important source of carotenoids [8,12,60,62]; as the yellow or orange color of the pulp indicates high carotene content [63]. Azevedo et al [60] identified several carotenoids present in the pulp of several species and varieties of pumpkins, among which are neoxanthin, violaxanthin, lutein, zeaxanthin, α-cryptoxanthin, α-carotene, β-carotene, and ζ-carotene.…”
Section: Nutritional and Phytochemical Composition Of Pumpkinsmentioning
confidence: 99%